2007
DOI: 10.1007/s00213-006-0661-3
|View full text |Cite
|
Sign up to set email alerts
|

Continuous exposure to the competitive N-methyl-d-aspartate receptor antagonist, LY235959, facilitates escalation of cocaine consumption in Sprague–Dawley rats

Abstract: These data are consistent with hypo-glutamatergic consequences of repeated cocaine exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 66 publications
5
15
0
Order By: Relevance
“…Numerous studies have also revealed adaptations in the NMDA2A receptor following repeated cocaine exposure (i.e., Hemby et al 2005a,b;Zhang et al 2007) and recent work suggests that this gene may play an important role in integrating dopamine-glutamate signaling which has been speculated to promote the long-lasting behavioral effects associated with chronic cocaine exposure (Liu et al 2006). Indeed, pharmacological manipulation of the NMDA receptor modulates cocaine-seeking behavior (Backstrom and Hyytia 2007) and escalation of cocaine consumption (Allen et al, 2007). Notably, one of the novel non-circadian related genes identified here is Park2 which has been shown previously to inhibit amphetamineinduced dopamine release and glutamate neurotransmission (Benavides et al 2003) suggesting that it may also be a candidate for integrating dopaminergic and glutamatergic signaling.…”
Section: Cocaine-responsive Gene Expression Of Non-circadian Genesmentioning
confidence: 99%
“…Numerous studies have also revealed adaptations in the NMDA2A receptor following repeated cocaine exposure (i.e., Hemby et al 2005a,b;Zhang et al 2007) and recent work suggests that this gene may play an important role in integrating dopamine-glutamate signaling which has been speculated to promote the long-lasting behavioral effects associated with chronic cocaine exposure (Liu et al 2006). Indeed, pharmacological manipulation of the NMDA receptor modulates cocaine-seeking behavior (Backstrom and Hyytia 2007) and escalation of cocaine consumption (Allen et al, 2007). Notably, one of the novel non-circadian related genes identified here is Park2 which has been shown previously to inhibit amphetamineinduced dopamine release and glutamate neurotransmission (Benavides et al 2003) suggesting that it may also be a candidate for integrating dopaminergic and glutamatergic signaling.…”
Section: Cocaine-responsive Gene Expression Of Non-circadian Genesmentioning
confidence: 99%
“…Using this schedule, it has been reported many times that after a period of drug self-administration, the motivation of the animals for drugs can increase. Thus, animals with a history of escalated cocaine use were found to respond at higher levels than animals that had limited cocaine access (Paterson and Markou 2003;Allen et al 2007;Larson et al 2007;Wee et al 2008Wee et al , 2009Orio et al 2009;Hao et al 2010, but see Quadros and Miczek 2009). This effect has subsequently also been found for other drugs of abuse, including methamphetamine (Wee et al 2007) and heroin .…”
Section: Increased Motivation For Drugsmentioning
confidence: 86%
“…Indeed, resistance to extinction has been observed in heroin-withdrawn rats with a history of extended access to heroin self-administration (Ahmed et al 2000;Doherty et al 2009). However, escalation of self-administration does not seem to be a prerequisite for resistance to extinction because extended access to cocaine or methamphetamine self-administration does not result in increased responding in extinction (e.g., Mantsch et al 2004;Sorge and Stewart 2005;Kippin et al 2006;Allen et al 2007;Knackstedt and Kalivas 2007;Rogers et al 2008). Interestingly though, gradual increases in responding for cocaine during periods of explicit nonavailability of the drug have been observed in subgroups of rats that also display other signs of addiction-like behavior after prolonged cocaine self-administration experience (DerocheGamonet et al 2004;Belin et al 2009).…”
Section: Resistance To Extinctionmentioning
confidence: 99%
“…In addition to the facilitation of escalation, continuous exposure to LY235959 leads to post-escalation "upward" shifts in a cocaine dose-response curve (Allen et al, 2007a) and increases in responding for cocaine under a PR schedule of reinforcement (Allen et al, 2007b). All together, these data suggest that cocaine produces larger effects on post-consumption measures (e.g., escalation, break point) when administered together with an NMDAR antagonist.…”
Section: Introductionmentioning
confidence: 92%
“…Similarly, blockade of NMDARs with either LY235959 (Allen et al, 2007a,b) or dizocilpine (Allen, 2014) facilitates (rather than prevents) the escalation of cocaine consumption that occurs when rats self-administer cocaine in long-access sessions. This effect is most clearly demonstrated when the NMDAR antagonist is administered continuously via osmotic minipump; rats given pre-session injections with LY235959 show marked disruptions in behavior (despite high rates of intake in some subjects; Allen et al, 2007a).…”
Section: Introductionmentioning
confidence: 98%